دراسة مقارنة لتقييم مدى ارتباط نتيجة تحليل بولتون ببعض الملامح الإطباقية - حسن حازم; نور الله عبد الوهاب; الزيتاوي عمرو (Latakia University Journal -Medical Sciences Series, 2019)
Background and objectives: Orthodontic treatment aims to achieve ideal occlusion, and this is achieved by fulfilling the six keys of ideal occlusion laid out by Andrews. But because of the importance of the harmony between upper and lower teeth sizes, this harmony was considered the seventh key of ideal occlusion. This study aims to investigate the differences between Bolton’s analysis (both anterior and overall ratios) values in malocclusion patients of the three Angle’s classes and the normal values, in addition to determining the correlation between some occlusal features (overjet, overbite, midline shift and upper and lower dental discrepancies) on one hand, and Bolton’s analysis values on the other hand. Materials and methods: These variables were studied in 46 dental casts for patients of Department of Orthodontics and Dentofacial Orthopaedics in Tishreen University, then T-test and ANOVA test were applied in addition to calculating Pearson’s correlation coefficient to get the results. Results: Results showed a statistically significant difference between the average value of Bolton’s anterior ratio in the whole sample and the normal value, and between the average value of Bolton’s anterior ratio in class I group and the normal value. As for the correlation between the values of Bolton’s anterior and overall ratios and the amount of the studied occlusal features, there were several correlations in different directions and intensities. Conclusions: The results indicate that there is a relationship between some occlusal features and Bolton’s analysis values, which emphasizes the need to treat teeth-size discrepancy if it exists in order to achieve good occlusion in the patient. مقدمة البحث وأهدافه: تهدف المعالجة التقويمية إلى الوصول إلى إطباق مثالي، ويتم الوصول إليه من خلال تحقيق مفاتيح الإطباق المثالي الستة التي وضعها أندروز، لكن ولأهمية وجود انسجام بين حجوم الأسنان العلوية والسفلية تم اعتبار هذا الانسجام مفتاحاً سابعاً للإطباق المثالي. تهدف هذه الدراسة إلى تحري وجود اختلافات في قيم تحليل بولتون (بنسبتيه الجزئية والكاملة) عند مرضى سوء إطباق من أصناف أنجل الثلاثة عن القيم الطبيعية، إضافة إلى دراسة ارتباط بعض الملامح الإطباقية (التغطية والبروز وانحراف الخط المتوسط والانسجام السني القاعدي العلوي والسفلي) مع قيم تحليل بولتون. المواد والطرائق: تمت دراسة هذه المتغيرات في 46 مثالاً لحالات مرضى مراجعين لقسم تقويم الأسنان والفكين بجامعة تشرين، وتم إجراء اختبارات T-test و ANOVA واستخراج معاملات الارتباط لبيرسون للوصول للنتائج المطلوبة. النتائج: أظهرت النتائج وجود فرق ذي دلالة إحصائية بين متوسط قيم نسبة بولتون الجزئية في كامل العينة والقيمة الطبيعية، وأظهرت أيضا وجود اختلاف بين متوسط قيم نسبة بولتون الجزئية لحالات الصنف الأول والقيم الطبيعية. أما فيما يتعلق بالعلاقة الارتباطية بين قيم نسبة بولتون الجزئية والكاملة من جهة ومقدار كل من الملامح الإطباقية المدروسة من جهة أخرى فقد كانت هناك عدة ارتباطات باتجاهات وشدات مختلفة. الاستنتاجات: تشير النتائج إلى وجود علاقة بين بعض الملامح الإطباقية ووجود خلل في قيم تحليل بولتون، مما يؤكد على ضرورة علاج الخلل في حال وجوده من أجل الوصول إلى علاقة إطباقية جيدة عند المريض.